Fiatal kutatás keres korban hozzá illő paradigmát. Társadalom és természeti környezet kölcsönhatásának elméleti modelljei és a Balaton multidiszciplináris kutatása - Molnár, Gábor (Acta Scientiarum Socialium, 2013)
Young research seeks age appropriate paradigm. Theoretical models for the interaction between society and its natural environment and the multidisciplinary research of Lake Balaton In searching for an adequate theoretical paradigm for the relationship between society and its natural environment, the paper analyses and compares Niklas Luhmann’s and Bruno Latour’s constructions of this relation. The aim of the comparison is to determine which of them can provide a more suitable theoretical basis for the social sciences to be able to join effectively in a multidisciplinary human ecological research program.